(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2022)
We present preliminary work optimising 3D printed porous triply periodic minimal surface (TPMS) structures, formed using Thermoplastic Polyurethane (TPU) elastomer with Fused Filament Fabrication (FFF). We examine the compressive properties of a Split P TPMS structure for changes in the unit cell porosity for a fixed unit cell size of 10mm. Preliminary results highlight opportunities to apply Split P TPMS structures made in TPU to mimic properties of medical grade foams typically found in diabetic foot orthotics, and through porosity adjustment, can be tailored across a greater range of compressive strengths. Such structures may find usefulness in creating a new generation of diabetic foot insoles whereby the compressive strength can be tailored to the unique loading conditions of the user.